China and the peace of Asia. Ed. and with a forew. by A. Buchan. [With contribs by W.P. Bundy, J, Chauvel, R. Scott a.o.] (Chatto & Windus, 1965)
With bibliogr. and tabs. Publ. for the Institut for strategic studies.